Energy distribution in formant bands for arabic vowels - Mohamed Farchi; Karim Tahiry; Soufyane Mounir; Badia Mounir; Ahmed Mouhsen (Institute of Advanced Engineering and Science, 2019)
The acoustic cues play a major role in speech segmentation phase; the extraction of these indexes facilitates the characterization of the speech signal. In this work, we aim to study Arabic vowels (/a/, /a:/, /i/, /i:/, /u/ and /u:/), especially the long ones. We are interested in characterizing this type of vowels in terms of time, frequency and energy. The cues extracted and analyzed in this work are: segment length, voicing degree and formants values.